Comparison of clinical evaluation of post-operation patients of open reduction internal fixation (ORIF) plating proximal humerus using conventional methods and minimally invasive plate osteosynthesis (MIPO) in Surabaya - Musa Arafah; Heri Suroto; Erwin Ramawan (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACT There are several kinds of approaches in the installation of implants for proximal humerus therapy. At present, minimally invasive surgery is gaining in popularity; this is supported by increasingly good technological developments to optimal the postoperative outcome is more optimal than conventional methods. This study used an analytic retrospective design with samples of post-ORIF Plating MIPO and posted ORIF due to proximal humeral fracture. Evaluation using the instrument of VAS Score, ASES Score, and measurement of range of motion. Statistical tests showed that there was a significant difference in the VAS score at the first evaluation (p = 0.002); the last review was not significant. In ASES Score, abduction, flexion, and external rotation, there were significant differences during the first and last evaluations. Adduction, extension, and internal rotation have no significance. The method of minimally invasive plate osteosynthesis (MIPO) on proximal humeral operative fracture therapy had a better clinical outcome and operating time than post-ORIF plating with conventional methods. As well, the MIPO method on proximal humeral fracture operative therapy based on radiological features has the same union rates compared to post ORIF plating with conventional methods. The method of minimally invasive plate osteosynthesis (MIPO) in operative therapy of neer 2 and 3 proximal humeral fracture has a better clinical outcome than conventional methods.Keywords: proximal humeral fracture, Minimal Invasive Plate Osteosynthesis (MIPO), Open Reduction Internal Fixation (ORIF)Correspondence to: musa_shi911@yahoo.com